Metode Fuzzy Logic Untuk Evaluasi Kinerja Pelayanan Perawat ( Studi Kasus : RSIA Siti Hawa Padang ) - Anas Aklani, Syaeful (Jurnal EDik Informatika, 2014)
On the Eve RSIA Hospital Padang, Nurse is providing primary care and first at the hospital before the doctor, with a good performance and a professional nurse the hospital can provide maximum service to patients or visitors to the Padang and Eve RSIA yet a way to assess the performance of nursing care so the management can not determine what policies need to be taken to evaluate the performance of nurses, based on this and the above information, the author tries to create and design a fuzzy logic to assist management in evaluating the performance of hospital nurses in service.So the evaluation is expected and help assess the performance of management and employees to nurse and take the next step what the results of the performance of nurses there had been no evaluation of the performance of the nursing service. This is an interesting writer to investigate and develop, assess all the existing problems in order to solve the problem.Keywords: Fuzzy Logic, Artificial Intelligence, Nursing